1980
DOI: 10.1007/bf01256639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noradrenaline and vanadium on Na+K+-activated ATPase in rat cerebral cortex synaptosomal preparation

Abstract: The effect of l-noradrenaline and vanadate on the activity of Na+K+-activated ATPase was studied on synaptosomal brain cortex preparation. Using neutron activation analysis it was found that the rat cerebral cortex synaptosomal preparation contains 0.16 microM vanadium. The concentration of vanadium needed to reduce enzyme activity by 50% proved to be 2 x 10(-6) M. Evidence has been provided that the increase by noradrenaline of enzyme activity in synaptosomal preparation depends on the presence of an inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…It is well known from several studies that noradrenaline is capable of increasing Na+ ,K+-ATPase activity in different parts of the brain (Schaefer et al, 1972;Yoshimura, 1973;Godfraind et al, 1974;Lee and Phillis, 1977;Adam-Vizi et al, 1979). Recently we have shown that vanadate can inhibit Na+,K+-ATPase activity without affecting Mgz+-ATPase activity in a synaptosomal preparation from rat brain cortex (Adam-Vizi et al, 1980). This inhibition could be partly reversed by noradrenaline, which is in line with an earlier finding of .…”
Section: M)supporting
confidence: 89%
See 1 more Smart Citation
“…It is well known from several studies that noradrenaline is capable of increasing Na+ ,K+-ATPase activity in different parts of the brain (Schaefer et al, 1972;Yoshimura, 1973;Godfraind et al, 1974;Lee and Phillis, 1977;Adam-Vizi et al, 1979). Recently we have shown that vanadate can inhibit Na+,K+-ATPase activity without affecting Mgz+-ATPase activity in a synaptosomal preparation from rat brain cortex (Adam-Vizi et al, 1980). This inhibition could be partly reversed by noradrenaline, which is in line with an earlier finding of .…”
Section: M)supporting
confidence: 89%
“…It was suggested that the stimulatory effect of noradrenaline on enzyme activity might be related to its ability to reverse the inhibition of the enzyme caused by vanadate Adfim-Vizi et al, 1980). The suggestion seemed to be very feasible, particularly as when vanadium-free ATP was used as substrate noradrenaline was no longer able to increase enzyme activity in synaptosomes unless they had been previously exposed to vanadate (Adam-Vizi et al, 1980).…”
Section: M)mentioning
confidence: 99%